Coupled Electrodeposition of Fe–Co–W Alloys: Thin Films and Nanowires - Maliar, Tatjana; Cesiulis, Henrikas; Podlaha, Elizabeth J. (Frontiers in Chemistry, 2019)
The electrodeposition of Fe–Co–W alloys was examined using a rotating cylinder Hull cell and conditions were determined to create nanowires. The metal ion reduction mechanism was a combination of induced and anomalous codeposition, with water reduction as a gas evolving side reaction, rending deposition into recesses a challenge. In thin film deposition, under kinetic control, the addition of Fe ions into the electrolyte, greatly reduced the Co partial current density and thus it’s content in the deposit. The change of Co partial current density was attributed to an anomalous codeposition behavior, but it had a minimal effect in changing the W wt % in the deposit, despite the expected inducing characteristic of Fe when codeposited with tungsten. Deposition conditions were determined to electrodeposit Fe–Co–W nanowires having similar concentration as the thin films. Nanowires were electrodeposited into polycarbonate membranes under pulsed current at room temperature.